Research on the framework of curriculum ideology and politics in the teaching of Surgery in higher vocational students (课程思政元素融入高职外科学教学的路径研究) - ZHOU Wei (周维); CAO Bo (曹波); RU Guanpu (茹官璞); ZHANG Jia (张佳); ZHAO Yuhuan (赵玉焕) (Association of Integrative Nursing, 2023)
Objective To investigate the connotation and characteristics of curriculum ideology and politics, and to summarize the practice framework of curriculum ideology and politics in the teaching of Surgery in higher vocational students. Methods Students major in clinical medicine from 4 classes in academic year of 2022 were randomly divided into the study group and control group. The literature research method based on educational network and academic journals was adapted to in the teaching of curriculum ideology and politics in the control group. The action research method was used in the teaching of curriculum ideology and politics in the study group. The teaching efficacy was evaluated and measured between two groups. Results The students satisfaction with teaching was 93. 24%(69/74)in the control group and 98. 80%(82/83)in the study group. The number of questions answered was 1324 in the study group and 983 in the control group. Conclusion The curriculum ideology and politics by using action research method is effective to improve the independent learning of higher vocational students and teaching quality of Surgery. (目的 探索课程思政的内在特点和科学内涵, 总结课程思政在高职外科学教学的实践路径。方法 选择2022级三年制临床医学4个班, 分为为研究组和对照组。对照组班级主要通过教育网络、学术期刊等方式将课程思政元素融入外科学课程教学中; 研究组班级采用行动研究法进行课堂思政教学。评价两组教学效果。结果 对照组班级学生74人, 听课满意度为93. 24%(69/74); 研究组班级学生83人, 听课满意度为98. 80%(82/83)。观察期内研究组班级学生课堂回答问题次数为1324人次, 高于对照组班级学生回答问题次数的983人次。结论 采用行动研究法将课堂思政融入外科学课程教学中, 能够提高学生自主学习积极性, 提高教学质量。)